Supramolecular interpenetrated Faujasite-like crystals from [4+4] imine cages - Lauer, Jochen; Zhang, Wen-Shan; Elbert, Sven; Rominger, Frank; Schröder, Rasmus R.; Mastalerz, Michael (Chemistry - a European journal, 2025)
In recent years, porous organic cages have gained in importance, inter alia, due to their ability to be processed from solution. Especially the packing of the cages in the solid state has a significant effect on the porosity. Therefore, it is important to be able to control the packing pattern either by crystallization conditions or the interaction of molecular units, defined as crystal engineering synthons. Here, tribromoarene subunits as such are incorporated into cage structures, namely a [2+3] and a [4+4] imine cage, to study the reliability of this subunit as crystal engineering synthon. Several solvatomorphs of both cages were studied by single-crystal X-ray diffraction and packing patterns thoroughly analyzed. Among those solvatomorphs an interpenetrated Faujasite-type supramolecular arrangement is found.